Strategic Networking Models of Small and Medium Sized Enterprises in Croatia - Čolović, Zorica Krželj (Oeconomica Jadertina, 2017)
Due to limited financial and non-financial resources they lack the adequate organizational characteristics such as experts, high rate of risk, lack of information about market threats and no economies of scale. In order to overcome these barriers hotel enterprises are forced to rely on the cooperation with other enterprises and tourism related organizations creating in such a way strategic networks. A strategic network refers to groups of enterprises and individual subjects that through joint efforts aim to achieve a competitive advantage, something that through individual efforts would be very difficult. The hotel enterprises, which use some form of networking, have realized that by cooperating with their competitors, suppliers and customers, as well as with enterprises from other industries, allows them to strengthen their internal weaknesses. The purpose of this paper is to show which forms of strategic networking are being used by small and medium hotel enterprises in Croatia. Based on the empirical research conducted on 250 small and medium sized hotel enterprises in Croatia in 2012, the goal was to determine which forms of strategic networking hotel enterprises use. The results show that the analyzed enterprises in Croatia use mostly a cluster based form of strategic networking.
Keywords: small and medium sized hotel enterprises; strategic networking; cluster; strategic partnership; strategic alliances